Chloride Induced Stress Corrosion Cracking (CISCC) of austenitic stainless steel under thermal insulation at ambient temperature - Sivanathan, P. (Medwell Journals, 2018)
Based on recent case study from petrochemical industry vessel leakage incident was taken to investigate failure of Chloride Induced Stress Corrosion Cracking (CISCC) of austenitic stainless steel 304. The objectives of this research was to investigate the reasons for CISCC failure of austenitic stainless steel 304. To simulate CISCC initiation of austenitic stainless steel 304 in different chloride concentration environment at ambient temperature. In this study, ASTM G-30 U-bend standard test method was used to evaluate factors that affect the CISCC of austenitic stainless steel 304. Total of 6 U-bend specimen were prepared with 200, 4000, 5000, 6000, 7000 and 8000 ppm of chloride concentrations. All these specimens were immersed in sodium chloride aqueous solutions for 8 months period to determine the parameters which leads to appearance of initiations crack mode. The laboratory experiment then repeated with the same specimens with 50,000 ppm chloride concentration for another 3 months. However, after cleaning the U-bend specimen and conducted dye penetrant inspection there were no appearance of initiation of crack found in any of specimens. Non-Destructive Testing (NDT) is one of assessment method used for detecting the CISCC susceptibility. The dye penetrant testing was used to identify the crack but invisible on the surface of the specimens. As a result, no initiation of crack found in this research from a metallurgical failure investigation of CISCC at ambient temperature. Thus, CISCC requires a long period exposure time for a rough surface finish of austenitic stainless steel 304 to form localized corrosions to lead the cracking mechanisms which is a complex process. Â© Medwell Journals, 2018.